Civil Society and its Place in the Constitution of Nepal - Dahal, Kapilmani (Journal of Political Science, 2019)
Civil society is a non-political sphere and a voluntary organization made from individuals. It lies as an intermediary layer between individuals and families on the one hand and state institutions on the other hand. Civil society has been becoming a hot matter in the system. Its place is not same everywhere. Some developed countries have been provide democratic atmosphere to develop it and have been ignoring it. Constitution as fundamental law of the land is a major tool providing space for civil society. In the context of Nepal civil society organizations, persons, movements or other forms of civil societies have been politicizing and they are ignoring their own values and status, which may be harmful to the effective functioning of democracy. In another context of Nepal books and articles have been written, researches are also conducted but the relation and place of civil society to constitutional provisions has not been mentioned yet. So this study has been made to link civil society to constitution of Nepal. Finally it drew conclusion that Constitution of Nepal is implementing and it has addressed some place for civil society but unfortunately some limitations made on constitution and politization of civil society has made civil society a believeless variables in Nepal. To draw the conclusion in this study descriptive analytical and content analysis methods has been used and information has been taken from secondary method.